2006
DOI: 10.1017/s0265021505002206
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral state monitor, a new small handheld EEG monitor for determining depth of anaesthesia

Abstract: When used for day-surgery anaesthesia without muscle relaxation, CSI and BIS show similar patterns and numerical values but with the incidence of occasionally large discrepancies between pair-wise readings. Which monitor is the more dependable remains to be established and cannot be implied from this initial explorative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
0
21
1
2
Order By: Relevance
“…Utrzymanie BIS w zakresie 40-60 zapewnia głęboki poziom depresji świa- T1 T2 T3 T4 T5 T6 T7 T8 MAP (mm Hg) domości obarczony ryzykiem jej powrotu u znieczulanych chorych [15]. Niniejsze obserwacje w pełni potwierdzają przydatność monitorowania BIS podczas endowaskularnego zaopatrywania tętniaków wewnątrzczaszkowych, zwłasz-cza że stwierdzono istotną korelację między jego wartością i stężeniem środków hipnotycznych [15,16]. Uważa się, że BIS pozwala na prowadzenie kontroli poziomu wyłączenia świadomości [16].…”
Section: Dyskusjaunclassified
“…Utrzymanie BIS w zakresie 40-60 zapewnia głęboki poziom depresji świa- T1 T2 T3 T4 T5 T6 T7 T8 MAP (mm Hg) domości obarczony ryzykiem jej powrotu u znieczulanych chorych [15]. Niniejsze obserwacje w pełni potwierdzają przydatność monitorowania BIS podczas endowaskularnego zaopatrywania tętniaków wewnątrzczaszkowych, zwłasz-cza że stwierdzono istotną korelację między jego wartością i stężeniem środków hipnotycznych [15,16]. Uważa się, że BIS pozwala na prowadzenie kontroli poziomu wyłączenia świadomości [16].…”
Section: Dyskusjaunclassified
“…The CSI and BIS show similar patterns and numerical values, but large discrepancies between pair-wise readings have All values are given as the mean ± standard deviation (SD) with the range given in parenthesis No significant differences were observed between the bispectral index (BIS) and the cerebral state index (CSI) occasionally been observed [4]. In one study on patients under propofol and remifentanil anesthesia, the CSI indicated that 13% of the patients were awake during parts of the course, despite being clinically sleep; these patients were correctly identified with the BIS [8].…”
Section: Discussionmentioning
confidence: 99%
“…Due to these different calculation algorithms, these indices may be different during anesthesia. Very few studies on the CSI have been published [4][5][6][7][8][9], and none of these have compared the BIS and CSI in patients receiving propofol-fentanyl-nitrous oxide anesthesia. The aim of the study reported here was, therefore, to compare the BIS and CSM (CSI) during propofol-fentanyl-nitrous oxide anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…E 2 represents the effect at sevoflurane concentrations from the plateau value to the maximal value while E 1 remains constant. values with both monitors during administration of propofol and inhalational agents [1][2][3][5][6][7] . However, our study is the first clinical investigation of pharmacodynamic modeling using the CSI for adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most extensively validated device used for this purpose is the bispectral index (BIS) monitor (Aspect Medical System, Newton, MA, USA). The cerebral state index (CSI), which is obtained by a cerebral state monitor (CSM TM Danmeter, Odense, Denmark), was recently introduced as a measure of the hypnotic component of anesthesia, and its usefulness has been previously evaluated [1][2][3][4][5][6][7] . However, there are no reports regarding the dose-response relationship between sevoflurane concentration and its effect in adults measured with CSI.…”
Section: Introductionmentioning
confidence: 99%